“Четвертий поділ” Польщі і встановлення радянського тоталітарного режиму в Західній Україні - Даниленко, В. (З архівів ВУЧК-ГПУ-НКВД-КГБ, 2004)
The present article was based on the unknown documents of the Branch state archive of Security service of Ukraine and showed the first phase so called “sovietizashion” (establishment of Soviet regim) of Western Ukraine after being joined to the USSR in the September 1939. The author investigeted the measures used to arrange the 800-meter borderland between the USSR and Third Reich.